Dupilumab treatment has no effect on the nasal microbiome in patients with NSAID-exacerbated respiratory disease: a longitudinal pilot study - Bartosik, Tina; Pjevac, Petra; Séneca, Joana; Morgenstern, Christina; Arnoldner, Tamara; Gangl, Katharina; Sinz, Christoph; Campion, Nicholas James; Tu, Aldine; Stanek, Victoria; Bangert, Christine; Schneider, Sven; et al. (Frontiers in Immunology, 2025)
BackgroundNon-steroidal anti-inflammatory drugs-exacerbated respiratory disease (N-ERD) affects up to 10% of patients suffering from nasal polyps and has a severe impact on quality of life. Dupilumab, a monoclonal antibody targeting the IL-4 receptor α chain, leads to symptom relief and reduction in nasal type 2 mediator levels. Here, we investigated the impact of dupilumab treatment on the composition and diversity of the nasal microbiome.MethodologyNasal microbiome was analyzed by 16s rRNA gene amplicon sequencing in 28 patients before, 4, 12, and 24 weeks after dupilumab therapy.ResultsAfter stringent decontamination and removal of patients whose samples contained less than 500 reads at ≥ one of the four visits, full datasets from 8 out of 28 patients remained for downstream analysis of microbiome data. All 8 patients showed significant reduction in TPS (total polyp score; p=0.0078) and an improvement in SNOT-22 (Sino-nasal outcome test-22, a quality of life questionnaire; p=0.0781) after dupilumab therapy. During 24 weeks of dupilumab therapy, there were no major changes in microbiome diversity or composition observed (Shannon index: V1-V4:p-adj=0.25, Chao 1 Index V1-V4:p-adj=0.31), and only 2 out of 8 patients showed a decrease in staphylococci abundance.ConclusionsMore than 70% of the samples did not pass quality control, this warrants further refinement of nasal microbiome sampling techniques and mandatory guidelines on stringent quality control for analysis of this low biomass data in future. Furthermore, dupilumab did not have an impact on microbiome diversity or composition.